Characteristics of the steps in the approach phase of the long jump between blind and elite athletes - Padulles, J. M.; Torralba, M. A.; Padulles, X.; Olsson, H. J.; Garcia, A.; De Fuentes, M. L.; López, J. L.; Theodorou, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Athletics is one of the emblematic sporting disciplines for people with disabilities and the one that attracts the largest numbers of participants and the widest range of events. It develops an spatial-temporal physical skills, and is a key sport for blind people in these areas. The long jumper during the approach run has three primary tasks to perform: to develop a maximal manageable horizontal velocity that can be used effectively during the take-off; to adjust the position of the body during the final few steps to bring it in an optimal take-off position with minimum loss of horizontal speed and to precisely adjust step length so that foot placement at jump take-off is as close as possible to the distal edge of the jump table from which the jump is measured (Hay, 1986; Hay and Koh 1988; Theodorou et al. 2010). Purpose: The purpose of this study is to compare the running approach to the take-off in long jump male blind athletes, in the final of the Paralympic Games London 2012 with elite athletes and to identify the differences observed in F11 category. Methods: It was performed a kinematic analysis in a group of 11 athletes. The variables analysed in the last three strides (3L, 2L, 1L) of the approach run were: Stride velocity, SV (m/s); Stride frequency, SF (Hz); Stride length, SL (m); Stride time, ST (s). The best jump of each athlete was selected for further analysis. Data collection was performed using 4 high-speed cameras Casio Exilim F1 at a frequency of 300 Hz. The image analysis was performed with Dartfish Pro Suite 2010 software. The statistical analysis of the data was performed using PASW V.18.0.0 software. Results: 3 / 2 / 1 to last . SV(m/s); 8,25±0,41 / 8,34±0,38 / 8,43±0,33. SF(Hz); 3,93±0,37 / 4,00±0,32 / 4,53±0,34. SL(m); 2,11±0,24/ 2,28±0,28/ 2,12±0,14. ST(s); 0,25±0,02/ 0,25±0,02/ 0,22±0,01. Discussion: Horizontal velocity during the last three strides before take-off has been shown to have a high correlation with the official jump distance. When measuring Paralympic athletes, using the same biomechanical parameters used for measuring high-level athletes, a wide range of similarities in the patterns used and the correlation with jumping distances achieved can be found.